Posttranslational Modifications of the Histone 3 Tail and Their Impact on the Activity of Histone Lysine Demethylases In Vitro - Lohse, Brian; Helgstrand, Charlotte; Kristensen, Jan B. L.; Leurs, Ulrike; Cloos, Paul A. C.; Kristensen, Jesper L.; Clausen, Rasmus P. (PLOS ONE, 2013)
Posttranslational modifications (PTMs) of the histone H3 tail such as methylation, acetylation and phosphorylation play important roles in epigenetic signaling. Here we study the effect of some of these PTMs on the demethylation rates of methylated lysine 9 in vitro using peptide substrates mimicking histone H3. Various combinations with other PTMs were employed to study possible cross-talk effects by comparing enzyme kinetic characteristics. We compared the kinetics of histone tail substrates for truncated histone lysine demethylases KDM4A and KDM4C containing only the catalytic core (cc) and some combinations were characterized on full length (FL) KDM4A and KDM4C. We found that the substrates combining trimethylated K4 and K9 resulted in a significant increase in the catalytic activity for FL-KDM4A. For the truncated versions of KDM4A and KDM4C a two-fold increase in the catalytic activity toward bis-trimethylated substrates could be observed. Furthermore, a significant difference in the catalytic activity between dimethylated and trimethylated substrates was found for full length demethylases in line with what has been reported previously for truncated demethylases. Histone peptide substrates phosphorylated at T11 could not be demethylated by neither truncated nor full length KDM4A and KDM4C, suggesting that phosphorylation of threonine 11 prevents demethylation of the H3K9me3 mark on the same peptide. Acetylation of K14 was also found to influence demethylation rates significantly. Thus, for truncated KDM4A, acetylation on K14 of the substrate leads to an increase in enzymatic catalytic efficiency (kcat/Km), while for truncated KDM4C it induces a decrease, primarily caused by changes in Km. This study demonstrates that demethylation activities towards trimethylated H3K9 are significantly influenced by other PTMs on the same peptide, and emphasizes the importance of studying these interactions at the peptide level to get a more detailed understanding of the dynamics of epigenetic marks.